2001
DOI: 10.1046/j.1523-1755.2001.059002407.x
|View full text |Cite
|
Sign up to set email alerts
|

End-stage renal disease, atherosclerosis, and cardiovascular mortality: Is C-reactive protein the missing link?

Abstract: In uremic patients, the morbidity and mortality of cardiovascular disease are substantially higher than in the general population. This has led to the formulation of an 'accelerated atherogenesis' hypothesis in uremic patients and has been commonly linked with the metabolic alterations associated with uremia. Advancement in the understanding of the pathogenesis of atherosclerotic vascular disease now suggests a central contribution of inflammation to atherogenesis, with involvement of a number of key mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
250
4
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(276 citation statements)
references
References 58 publications
12
250
4
10
Order By: Relevance
“…29,30 hsCRP was elevated at baseline in our patients, the level of 5 mg/L was identical to the level of hsCRP at inclusion of patients into the 4D study. 29 In 4D, treatment with atorvastatin had a minimal effect on hsCRP level and this was modestly lowered by 10.9% in the treatment arm in our study.…”
Section: Discussionsupporting
confidence: 62%
“…29,30 hsCRP was elevated at baseline in our patients, the level of 5 mg/L was identical to the level of hsCRP at inclusion of patients into the 4D study. 29 In 4D, treatment with atorvastatin had a minimal effect on hsCRP level and this was modestly lowered by 10.9% in the treatment arm in our study.…”
Section: Discussionsupporting
confidence: 62%
“…The crucial role of chronic hyperglycemia in the development and progression of atherosclerosis and CVD events in patients with diabetes mellitus or renal disease is not debatable 38, 39, 40. However, the identification of AGEs in the atherosclerotic plaques of nondiabetic patients with coronary artery disease have magnified the importance of AGEs and oxidative stress in accelerating atherosclerosis 41.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiologic studies have shown an association between CRP and arteriosclerosis, thereby establishing a possible link among inflammation, arteriosclerosis, and malnutrition in patients with kidney disease (13,27,28). Thus, patients who have failed kidney transplants and are on HD exhibit a constellation of hematologic and biochemical abnormalities characteristic of a chronic inflammatory state, which is associated with increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%